CODESRIA Bulletin Online, No. 7, May 2023: Beyond Tinkering: Changing Africa’s Position in the Global Knowledge Production Ecosystem1 - Gebremariam, Eyob Balcha; Aboderin, Isabella; Fuh, Divine; Segalo, Puleng (CODESRIA Bulletin, 2023)
Africa’s position in the global knowledge production ecosystem needs to change significantly. African knowledge systems, languages, knowledge actors and institutions must take their rightful place in global thought processes. Even more critical is the central place that such repositioning is bound to have in upholding African dignity. In this essay, we argue that the current global ecosystem of knowledge production exhibits multiple layers of injustices and inequities entrenched in its orientations, institutions, policy and legal frameworks and practices. Over the past few decades, several initiatives in the name of ‘equitable partnership’ emerged to address aspects of unequal global knowledge production ecosystem challenges – as they manifest in the configurations of research collaborations between Africa (or the ‘global South’ broadly) and global North. Such efforts are commendable, but they have remained on the surface. They have mainly treated the visible symptoms of the problem, leaving the fundamental underlying layers of inequities in global research unaddressed. Most of the existing equitable partnership frameworks focus on altering the unequal division of labour and resources between African knowledge actors and their Euro-American counterparts (particularly researchers, funders and international development actors); addressing gaps in capacities and capabilities; ensuring accessibility of research outputs; and crediting researchers in authorship, among other things.2 While some of these initiatives have triggered tangible changes in policies, funding frames, practices, and consciousness,3 inequalities remain largely unresolved.4 Hence, developing new ways of identifying the problem and suggesting potential policies are necessary. Multiple layers of power imbalances We depict the existing knowledge production ecosystem as a set of concentric circles representing multiple layers of asymmetrical power relations. The first layer at the core of the concentric circle constitutes various forms of epistemic injustices and inequities. This is the most fundamental aspect of power asymmetry. Africa was and continues to be constructed through the ‘colonial library’ (Mudimbe 2020) as a dark and savage continent and an epistemically void and intellectually empty space. The series of civilising missions and colonialist endeavours were justified as requirements to fill the epistemic void with universalist knowledge streaming from Europe’s enlightenment and modernity. An enduring legacy of such an imagination of Africa through the lens of the colonial library is engraved in the ‘extraverted’ knowledge production ecosystem of the continent. (Hountondji 1990) Hountondji observes that extraversion became an essential feature of Africa’s research and scientific practices by assigning Europe as a source of theory and concepts and Africa as a field site for extracting raw data. African epistemologies are considered non-existent or are provincialised as ‘indigenous knowledges’ to confine their relevance to a particular context, whilst Eurocentric knowledges run free as universal. As a result, Eurocentric epistemic orientation became the dominant, if not the only, framework for studying anything related to Africa or, indeed, the world. The other side of the hegemonic Eurocentric ontological and epistemic orientation is the invisibilisation, discrediting and otherisation of African ontologies, cosmologies and epistemologies. Undoing the effects of hegemonic orientation is critical to achieving meaningful change. One way of doing so is centring African epistemologies in global knowledge production. The second layer of the concentric circle covers the vital role of discourse and language. At the discursive level, the dominant trend is depicting and problematising African realities as a ‘lack of something’, or the normalisation of ‘deficiency’ and ‘misery’. The normalised ‘deficit mentality’ engraved in Africa-facing research initiatives also deploys powerful and metaphorical characterisations of complex African realities to keep the colonial depiction intact. For example, in the social science literature that studies African societies’ socio-economic and political relations, African cultures are often described as the antithesis to anything considered ‘good’ and as a breeding ground for corruption, nepotism and greed by the political elites. Thandika Mkandawire calls this the ‘neopatrimonial school’, where narrow, ahistorical and stylised explanations of microlevel social relations within society are extrapolated to theorise the nature of African states. Such ‘methodological communalism’ (Mkandawire 2015) uses African communities as ‘a foundational unit of analysis’ to derive macro-level narratives that confirm the image of Africa in the ‘colonial library’. Image: The multiple layers of power imbalances in knowledge production in Africa ( See PDF file) Source: Authors, 2023 Such discursive presentation of Africa or the African is not unique to disciplines in sociology and politics. Other disciplines also have a similar characterisation of African realities, societies, cultures, etc. For example, the discipline of psychology has a long history of racist practices and theorising. The eugenics movement led to the brutal and inhumane treatment of African bodies to legitimise ‘scientific truths’ about the inferiority of African minds and cosmologies. These forms of racist theorising continue, as seen in a 2019 psychological study, now retracted by the publishing journal, concluding that South African coloured women have an increased risk of low cognitive functioning (Nieuwoudt, Dickie, Coetsee, Engelbrecht and Terblanche 2020). In addition to the discursive construction of Africa, the second layer also captures the dominance of colonially imposed languages in education, research, and knowledge production. In almost all African countries, colonially imposed languages (mainly English, French, and Portuguese) serve as the primary, if not the only, mediums of instruction in higher education. One of the lasting legacies of colonial relations in the African context is rendering African languages epistemically irrelevant, particularly for research and education in higher education institutions. The epistemic violence of imposing European languages created a hierarchy of languages, cultures and identities. Kenyan scholar Ngȗgȋ wa Thiang’o shared his experience of 1950s Kenya where English was imposed as a medium of instruction at the expense of local Kenyan languages. Ngȗgȋ argues that after the legally sanctioned imposition, the English language became ‘… more than a language, it was the language: and all the other [languages] had to bow before it in deference’ (wa Thiong’o 2005). As a result, despite their role as sources of knowledge and wisdom, African languages are rendered irrelevant to the development of scientific knowledge both within the continent and worldwide. Almost all African universities organise their higher education and research using colonially imposed languages. African languages are often confined to a particular department or institute to be studied as a subject area than serving as a medium of instruction and scientific research. The third layer of power imbalance is the unidirectional gaze of knowledge production that inevitably locates Africa as an object of inquiry from the Western/Euro-American point of view. The unidirectional gaze has multiple lenses. It has a racialised lens where the ‘white man’ is almost always considered an expert and authoritative source of knowledge about African issues (Pailey 2020). The other lens is developmental and poverty-laden. The depiction of Africa in terms of what it lacks triggers research initiatives that for the most part try to fix the ‘development gaps’ in the continent. This gaze is premised on the idea of ‘development’ and the unquestioned rendering of Africa as developing or less developed. Development is often narrowly defined in terms of economic growth and ‘poverty reduction’. Research initiatives in African countries that do not conform to this narrow definition are considered less important or irrelevant. Currently, the Sustainable Development Goals (SDGs) serve as a de facto confirmation framework to decide the research agenda in African countries. For example, health-related research dominates African countries’ scientific publication outputs. On average, 49 per cent of scientific publications in 53 African countries (2017–2019) are in health sciences (UNESCO 2021). The Gambia has the highest proportion (89 per cent) of its scientific publications in health sciences. The dominance of health sciences has implications for the scope of inquiry into other relevant and timely issues, including in cross-cutting, strategic technology and engineering-related fields such as ICT, maths, statistics, physics, and astronomy (UNESCO 2021). The racialised, poverty-laden and unidirectional gaze of research is primarily designed to meet the interests and priorities of external actors. Its role in sustaining power asymmetries is inevitable. The fourth layer is the dominance of international research collaborations in the African research ecosystem. The above-mentioned layers of inequities and power imbalances underpin the overreliance on international research collaborations in Africa. International research collaborations are vital aspects of knowledge generation and the transferring of knowledge, skills and technologies, which help new ideas and orientations to flourish. However, what happens when a region’s research activities and outputs become excessively dependent on international collaborations? For example, in 2012, the ratio of scientific publications based on international collaborations in southern Africa, east Africa and central and western Africa was 79 per cent, 70 per cent and 75 per cent, respectively (Fonn, Ayiro, Cotton, Habib, Mbithi, Mtenje, and Ezeh 2018). Between 2017 and 2019, scientific publications based on international collaborations for central and eastern African countries rose to 88 per cent and 85 per cent for southern African countries. In contrast, for the 2017 to 2019 period, the ratio was 45.2 per cent, 34 per cent and 40 per cent for EU-28, OECD and Latin American countries, respectively (UNESCO 2021). The 2021 UNESCO Science Report shows that most African countries produce scientific publications in collaboration with authors from the United States, France, and the United Kingdom. The USA is the first collaborator for 19 African countries and the second for 18 African countries. Sixteen African countries have France as their first collaborator and three countries (Madagascar, Mali and Niger) have France as their second collaborator. Three African countries (Libya, Seychelles and The Gambia) have the UK as their first collaborator and 13 countries have the UK as their second collaborator. The same report by UNESCO confirms that the volume of intra-African collaboration pales in comparison to research collaborations with Europe and North America. South Africa is the only African country that stands out as the first collaborator for other African countries – specifically for Botswana, Eswatini, Lesotho, Namibia and Zimbabwe in southern Africa and for Nigeria. While international research collaborations are critical for expanding the frontiers of knowledge production for the entire human race, the fundamental inequalities upon which they are built on need to be addressed. The epistemic inequalities, power asymmetries and the one-sided nature of international research collaborations make them complicit in the problems rather than sources of change. The fifth layer of our concentric circle refers to the practical arrangements in research collaborations, including the unequal division of labour and unequal distribution of resources in research and knowledge production. Taken together, the preceding layers of inequities lead to a subordinate role for Africa-based knowledge actors both collectively and individually. Structural and institutional factors such as the demise of African universities during Structural Adjustment Programs (Obamba 2013) and the negligible financial commitment of African states to research capacity development contribute to the diminished role of African knowledge actors (Ezeh and Lu 2019). The subordinate role that most African knowledge actors assume in the practical arrangements within international collaborations is a major manifestation of the embedded power imbalances. Since this is the most visible aspect of inequalities, most equitable partnership frameworks aim to tackle it by proposing several remedies. Most of the remedies remain at project-level. Even if institutionalised, the remedies would fall short of addressing and challenging the core of the power imbalances. Tinkering with the Problem: Equitable Partnership Frameworks Most existing equitable partnership frameworks offer technical solutions that are primarily focused on the fifth layer of the concentric circle. For example, the Global Code of Conduct5 is concerned primarily with ‘ethics dumping’ and addressing the ‘capacity gap’ in research collaborations involving ‘resource-poor settings’. Normative values such as fairness, respect, care and honesty are proposed as key principles addressing the problem. The Good Practice Document (UKCDR 2022) – produced by the UK Collaborative on Development Research (UKCDR) and ESSENCE – in its turn aims to find ‘a balance between flexibility and equity’ and to provide ‘practical recommendations’ to overcome ‘barriers of equity’. For others, such as the Guide for Transboundary Research Partnerships6 and Research Fairness Initiative, the primary concerns are ‘organising transboundary research collaboration in an effective manner’ and ‘improving fairness, efficiency and impact’ of research collaborations. The most common solutions that existing equitable partnership frameworks propose include: fair distribution of resources and recognition in authorship, inclusion in research agenda-setting, research capacity building and strengthening of so-called ‘global South networks’. Along with the various initiatives, a few terminologies, principles and ideas also emerge. Some of the common terminologies include: ‘shared agenda setting’, ‘mutual learning’, ‘shared data and networks’, ‘clarified responsibilities’, ‘accountability to beneficiaries’ and ‘fair research contracting and co-financing’. At face value, these notions express valuable intentions and approaches – but without reference to the more fundamental power imbalances, they remain less meaningful or serve to obscure the need for more profound change. The diagnosis of the problem that informs the existing equitable partnership frameworks, and the solutions they provide, fall significantly short of addressing the complex layers of power imbalances. Therefore, they cannot help towards repositioning Africa’s role in the global science and research ecosystem. As we argued earlier, epistemic injustices and inequities are the fundamental problems. Addressing only the visible symptoms of the historically entrenched and epistemically installed problems can hardly take us forward. That is why we propose a new Charter Framework that will allow us to address the problem in a more systematic and transformative manner by taking international research collaborations as an entry point. Towards a Charter Framework The pursuit of change in the African knowledge production ecosystem can have multiple faces and trajectories. We believe radical change is necessary if we are to transform Africa’s position in the global science and research ecosystem. At present, we are in the process of co-designing a Charter Framework that will serve as a guide to address the multi-layered power imbalances outlined earlier. The added value of the Charter Framework is the diagnosis of the problem centring epistemic inequities and injustices and the intertwined relations among the various layers of problems. In a nutshell, the proposed Charter Framework can have three interrelated faces: A political framework: change is unthinkable without altering the relationship among actors and their relations towards resources. The existing system of knowledge production serves a set of interests that benefits several actors both within and outside the continent. These are financial, economic, political and ideological interests. Hence, if the Charter Framework is to become a useful input for radical change, it needs to serve as a political tool to reshape power relations, renegotiate partnerships, organise and contest normalised practices, and build the necessary institutional and collective muscle to reject practices that sustain any form of power imbalances. A policy initiative: the Charter Framework can also become an important policy initiative to alter normative practices, the values and missions of knowledge actors, and the consciousness and attitudes of individuals. As a policy initiative, the Charter Framework can also outline the necessary institutional arrangements, strategic orientations and practices of both organisations and individuals in the knowledge production ecosystem. Unless the political framework of altering power relations is transferred into the policy realm to shape practices, the ideals of the Charter Framework will remain empty slogans. An intellectual exercise: pursuing the Charter Framework both at the political and policy level needs a rigorous intellectual project of revisiting, analysing, and synthesising academic works by African and non-African scholars that called for a change in knowledge production. Such continuous debates, critical reflections, rethinking and unthinking will save us from reinventing the wheel and take relevant lessons from previous efforts with a similar mission. In conclusion, we believe that it is time to go beyond tinkering on the edges of the global science and research ecosystem. Transformative research collaborations between African and global north knowledge actors can be achieved only if we are ready to adequately understand the multiple layers of power imbalances and the manifold manifestations at every stage of knowledge production. We are embarking on this mission by formulating and co-producing a new Charter Framework that builds on the successes of existing equitable partnership frameworks and adds substantive value to vital issues that remain hidden. Notes This piece was initially drafted by Eyob Balcha Gebremariam and received substantive comments and inputs from all the other contributors. You can reach the authors at eyob.b.gebremariam@bristol.ac.uk; isabella.aboderin@bristol.ac.uk; divine.fuh@uct.ac.za; and segalpj@unisa.ac.za National Institute for Health and Care Research, 2021, Equitable Partnerships Guide, (https://www.nihr.ac.uk/documents/equitable-partnerships-guide/21955), 19 May 2023. Some examples include: UKCDR, 2022, Equitable partnerships: Lessons from practitioners. (https://www.ukcdr.org.uk/equitable-partnerships-lessons-from-practitioners/) 19 May 2023; Global Code of Conduct. (https://www.globalcodeofconduct.org/affiliated-codes/), 19 May 2023. We argue that these equitable partnerships efforts have not even considered a need for addressing more fundamental inequalities i.e. a rebalancing of the global scientific knowledge production ecosystem as a whole. We put forward our argument on this issue in a separate piece. Global Code of Conduct, (https://www.globalcodeofconduct.org/affiliated-codes/), 19 May 2023. Swiss Commission for Research Partnerships with Developing Countries (KFPE), A Guide for Transboundary Research Partnerships (3rd edition - 2018). (https://kfpe.scnat.ch/en/about_kfpe/uuid/i/13beb0f7-4780-5967-a257-bd6cc3d5e424-A_Guide_for_Transboundary_Research_Partnerships_3rd_edition_-_2018), 22 May 2023. Research Fairness Initiative. (https://rfi.cohred.org/), 19 May 2023.